Analysis of the radon concentrations in natural mineral and tap water using Lucas cells technique - Calin, M. R.; Ion, A. C.; Radulescu, I.; Simion, C. A.; Mincu, M. M.; Ion, I. (Journal of Environmental Engineering and Landscape Management, 2022)
The aims of this study were to determine the radon concentration in natural mineral and tap water and to estimate the resulting ingestion doses received by adults. Physical-chemical characteristics of water samples have also been investigated. In the last years have been an increase of water consumption of both, natural mineral and tap, many sources and producers being available on the market. Thus, the physical-chemical and radiologic parameters of water must be in compliance with the Drinking Water Directive (DWD). Thus, the study presents an assessment of the radioactivity due to 222Rn and 3H in several mineral natural water samples from the north region of Romania, but also in several tap water samples. The methods used were based on gamma spectrometry, gross alpha-beta measurements and beta spectroscopy, but also ICP-MS for chemical parameters. The results of this work showed that the geology and rock types clearly influence the water radon concentration. The radon concentration is lower in the water that passes through sedimentary rocks than that passing through granitic rocks. An important aspect of this work is to provide reliable information regarding radon and tritium concentrations. Radon concentration varied between 0.15±0.05 Bq/L and 11.35±2.97 Bq/L in the natural mineral water samples and between 0.17±0.05 Bq/L and 8.51±2.34 Bq/L in the tap water samples. An estimation of annual effective radiation dose based on the sample results was also made. Calculated values for ingestion dose due to regular consumption of water does not induce a health risk because of the intake of various radionuclides contained in the water. The maximum values being of 47.38 µSv/y. The determined values for the collected samples are below recommended reference levels, but more important aspect is that this study emphasise environmental sustainability in the investigated area.